Current perspective of plant-based diets on communicable diseases caused by viruses: a mini review - Wong, Carisa Su-Ann; Lim, Cheng Wei; Mohammed, Haruna Isa; Liew, Kong Yen; Tham, Chau Ling; Tan, Ji Wei; Chee, Hui Yee (Frontiers Media, 2022)
Communicable diseases are illnesses caused by pathogenic biological agents, including viruses, bacteria, fungi, parasites, and protozoa. Such diseases spread among people through contact with contaminated surfaces, bodily fluids, or blood products, or through the air, insect bites, or consuming contaminated food and beverages. Although some communicable diseases can be treated or prevented by taking medication and vaccines, there has been an increase in awareness of adopting a healthy diet to aid in the prevention and reversal of these diseases. One popular diet is a plant-based diet. Plant-based diets generally consist of vegetables, grains, nuts, seeds, legumes, and fruits, without any animal-source foods or artificial ingredients. Over the years, this diet has continuously increased in popularity. Reasons for following a plant-based diet are varied but include health benefits, such as improving immunity, and reducing the risk of heart disease, diabetes, and some cancers. Scientific evidence even shows that just an increased vegetable intake can decrease the occurrence of chronic diseases caused by viruses, such as hepatitis viruses, and reduce the risk of severe coronavirus disease 2019. Therefore, this mini review discusses the effectiveness of adopting a plant-based diet in ameliorating diseases caused by selected viruses and its limitations.